DESIGN OF ACADEMIC INFORMATION SYSTEM USING THE USER-CENTERED DESIGN METHOD (CASE STUDY AT SD N PAYUNGAN) - Devangie Putri Nabilla Tiara Sutrisna; Aditya Wahana; Puji Handayani Putri (JTH: Journal of Technology and Health, 2024)
An academic information system is a software system designed to help manage academic data and information more efficiently. However, this has not been implemented at SD N Payungan. This causes forgetting or loss of information because data is still managed manually, and double data input causes an increase in the size of files stored on the computer, resulting in slow device performance. Therefore, this research aims to design an academic information system using the User-Centered Design method. The UCD method is used to ensure that the system is built according to the needs of users, namely school admins, teachers, and student parents, so as to increase the efficiency and effectiveness of academic data management. The results of the research show that the information system built can run well in managing academic data. This is proven by the results of the number of respondents 33 people. System testing shows that the system functions well and suits users. In conclusion, the use of the User-Centered Design method to design an academic information system has proven to be helpful in producing a system that is efficient, easy to use, and fulfills the need to help manage school data. It is hoped that this User-Centered Design method can be applied in other schools that face similar problems.